ANALISIS KEBUTUHAN SUMBER DAYA MANUSIA DI INSTALASI REKAM MEDIS BERDASARKAN TEORI WORKLOAD INDICATORS OF STAFF NEED (WISN) GUNA MENUNJANG EFEKTIVITAS KERJA DI RUMAH SAKIT TNI AU DR. M. SALAMUN BANDUNG - Neni Rohaeni; Rizqy Dimas Monica; Encep Hada (UPPM Politeknik TEDC Bandung, 2019)
Based on preliminary study results, previous interviews and observations made by the authors are 18 medical record officers, some parts of medical record activities there are officers who concurrently work as in the coding section, assembling and analysis into the registration form so that the work received by the officer experienced a buildup of 10 medical record files (0.1%). The research method used is a descriptive method of quantitative approach. The research instrument used in this unstructured interviews, observations and documentation studies. The results of human resource calculations based on WISN theory in the outpatient registration and hospitalization required as much as 8 people while the number of officers available only 2 people so that it is necessary to replenishment 6 people, for other parts such as outpatient and hospitalization mix requires 1 person has been fulfilled, assembling, analysis requires 1 person has been fulfilled, coding 1 person has been fulfilled, and the 6 person filling section has been fulfilled. Preferably in a service evaluation meeting conducted 1 time a month discussing about human resources so that there is no human resources that concurrently work and create a buildup of work and monitoring and conduct routine evaluation so that every problem that occurs can be anticipated and resolved properly.